ANALISIS PEMILIHAN PEMASOK BERKELANJUTAN PADA PERUSAHAAN CAT MENGGUNAKAN METODE ANALYTIC NETWORK PROCESS (ANP) DAN TECHNIQUE FOR ORDER OF PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) - Apriyanti Hidayat (2023)
PT. XYZ is a manufacturing company that produces paint. The company uses Resin as one of the raw materials in paint production. The problem faced by the company is the absence of a specific evaluation system in supplier selection, resulting in delivery delays, the use of unsuitable transportation, risks of product damage, worker safety hazards, and ineffective waste management. This study aims to design criteria and sub-criteria for sustainable supplier selection in PT. XYZ and identify the best suppliers based on these sub-criteria using the Analytical Network Process (ANP) and Technique For Order Preference by Similarity to Ideal Solution (TOPSIS) methods. In this study, the cut-off points method is used to select relevant sub-criteria in decision-making. Out of the initial 15 criteria, only 11 sub-criteria were chosen across three perspectives: economic, environmental, and social. Supplier performance evaluation is conducted by assigning weights to each sub-criteria using the ANP method. The results reveal the highest priority order of sub-criteria for each criterion. Subsequently, the TOPSIS method is employed to determine the priority of Resin suppliers in PT. XYZ. The findings indicate that supplier A has the highest preference value, followed by supplier D, supplier B, and supplier C. Thus, this research provides recommendations for selecting the best suppliers based on the established criteria and sub-criteria. It is expected that the results of this study will help the company improve the effectiveness and efficiency of sustainable supplier selection processes while reducing risks and losses associated with improper supplier choices.